PRAGMATICS ELEMENT IN PRODUCT PROMOTION CONTENT THROUGH SHORT VIDEO PLATFORM TIK TOK, INSTAGRAM REELS, AND YOUTUBE SHORTS - Jacobus Rico Kuntag; Survey Sijabat (SEAN Institute, 2023)
This study aims to analyze pragmatic elements in product promotion content through short video platforms on social media. The research method used was content analysis, which consists of unitizing, sampling, recording/coding, reducing, inferring, and narration. A total of 30 product advertising videos were obtained from Indonesian business accounts. Ten short videos were selected from each of the three social media platforms: TikTok, Instagram Reels, and YouTube Shorts. The results of the study showed that pragmatic elements used in product marketing content on the four short video platforms vary, including the use of casual conversational language and direct audience interaction. However, there are differences in the use of pragmatic elements between the four platforms, as product marketing content on TikTok and Instagram Reels is dominated by humorous and surprising elements, whereas product marketing content on YouTube Shorts emphasizes creativity and attractive visual elements. The results of this research provide insight into how marketers select appropriate short video platforms to advertise their products, as well as create content that suits the audience's preferences.